2020
DOI: 10.2196/19861
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging Adherence Intervention for Adolescents and Young Adults with Chronic Kidney Disease: Pilot Randomized Controlled Trial and Stakeholder Interviews

Abstract: Background Up to one-third of adolescents and young adults (11-21 years old) with chronic kidney disease exhibit suboptimal rates of adherence to renal-protective antihypertensive medications. Mobile health interventions may promote higher adherence to these medicines in these individuals, but empirical research is needed to inform best practices for applying these modalities. Objective In this multiphase investigation, we developed and tested a theoret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Digitally delivered interventions would be able to be tailored to a patient's individual needs and could address multiple BCTs. The development of mHealth intervention apps that allow for several components of the COM‐B model to be targeted have been done in diabetes, hypertension, and chronic kidney disease 55–57 …”
Section: Discussionmentioning
confidence: 99%
“…Digitally delivered interventions would be able to be tailored to a patient's individual needs and could address multiple BCTs. The development of mHealth intervention apps that allow for several components of the COM‐B model to be targeted have been done in diabetes, hypertension, and chronic kidney disease 55–57 …”
Section: Discussionmentioning
confidence: 99%
“…This design is consistent with recent feasibility studies of self-management mHealth interventions for young people with a range of chronic conditions [ 59 , 111 - 115 ], including asthma [ 53 ]. Furthermore, recent randomized feasibility studies of such interventions for young people [ 116 , 117 ] and asthma specifically [ 44 , 118 ] have reported no significant difference in retention rates between intervention and control groups. Therefore, the feasibility of randomizing young adults was not considered a key parameter for this initial investigation in which feasibility of recruitment and retention were deemed more pertinent to focus on at this early stage.…”
Section: Discussionmentioning
confidence: 99%
“… 31 A study of 34 adolescents and young adults with CKD found improvements in electronically monitored adherence with the use of a 8‐week program of education and support text messages ( p = 0.04). 34 There was no significant change in self‐efficacy scores. In the TAKE‐IT randomized trial, 169 adolescents or young adults with kidney transplants received regular text messages, e‐mails and/or visual cue dose reminders, and third monthly face‐to‐face coaching sessions 12 months, resulting in significantly greater odds of taking medications at or near the prescribed time (OR 1.74; 95% CI 1.21–2.50).…”
Section: Using Digital Technologies To Improve Medication Adherence I...mentioning
confidence: 93%
“…There are few examples of text message programs rigorously assessed in people with CKD or kidney transplants, and these have been limited by small sample size and short duration 31 . A study of 34 adolescents and young adults with CKD found improvements in electronically monitored adherence with the use of a 8‐week program of education and support text messages ( p = 0.04) 34 . There was no significant change in self‐efficacy scores.…”
Section: Using Digital Technologies To Improve Medication Adherence I...mentioning
confidence: 99%